Production of crude pectinase from Aspergillus niger under solid state fermentation by using different agro wastes as substrates - Nor Asma Liyana, Jaais (Universiti Malaysia Sarawak, (UNIMAS), 2015)
Pectinase is well known for its utilisation in industries especially for food and beverages where it helps to enhance juice extract. This study emphasised on pectinase production by Aspergillus niger using three different substrates; rice husk, pineapple peel and banana peel under solid state fermentation. This study also focused on the effects of incubation period, initial moisture content and incubation temperature on the production of pectinase. The enzyme activity was determined by DNS method. The highest pectinase activity obtained from rice husk was at 6 days of incubation, 65% of initial moisture content and at temperature of 35·C, while the highest enzyme activity from banana peel was at 4 days, 65% initial moisture content and at 35·C temperature. Pineapple peel yielded the highest enzyme activity which was at 0.481 Vlml at 6 days incubation period, 70% initial moisture content and at temperature of30·C.